Medial-lateral translational malalignment of the prosthesis on tibial stress distribution in total knee arthroplasty: A finite element analysis - Zheng, Zhiqian; Liu, Yang; Zhang, Aobo; Chen, Hao; Wan, Qian; Zhong, Lei; Wang, Xiaonan; Han, Qing; Wang, Jincheng (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Poor prosthesis alignment during total knee arthroplasty could cause problems such as polyethylene spacer wear, leading to surgical failure and revision surgery. The problems caused by the malalignment of the tibial plateau prosthesis in the medial and lateral planes are unclear. We aimed to investigate the stress distribution and micromotion of the tibia when the tibial plateau prosthesis is translated 1 and 2 mm medially and laterally, respectively, using finite element analysis (FEA). Method: A non-homogeneous tibia model was created and load conditions when standing on two legs were applied using FEA to simulate the misaligned prosthesis. The stresses, stress distribution, and micromotion of the proximal tibia were analyzed in five positions of the tibial plateau prosthesis: Lateral-2 mm; Lateral-1 mm; Medium; Medial-2 mm; Medial-1 mm. Result: The maximum stress in the five groups with different misalignments of the platform was 47.29 MPa (Lateral-2 mm). The maximum micromotion among the five groups in different positions was 7.215 μm (Lateral-2 mm). Conclusion: When placing the tibial plateau prosthesis during total knee arthroplasty, an error of 2 mm or less is acceptable as long as it does not overhang.